2015
DOI: 10.1111/1467-9604.12086
|View full text |Cite
|
Sign up to set email alerts
|

The effects of choice in the classroom: Is there too little or too much choice?

Abstract: Motivation is a subject that is constantly discussed in the field of education. Teachers are taught not only to teach their students, but to motivate them to want to learn. As students get older, intrinsic motivation tends to decrease; therefore it becomes more difficult for teachers to motivate students (Ryan and Deci, 2000a). According to self-determination theory (Ryan and Deci, 2000a, 2000b), students' needs for autonomy, competence and relatedness must be met in order to experience positive social develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…Allowing students some choice in what they work on results in a diverse set of portfolio products that better reflect the individuals in the class. Practicing skills in a context relevant to students' own interests and goals can also help motivate them (Beymer & Thomson, 2015). In the seminar, students picked from a selection of assignments related to the content of the class each week.…”
Section: Forming a Data-science Identitymentioning
confidence: 99%
“…Allowing students some choice in what they work on results in a diverse set of portfolio products that better reflect the individuals in the class. Practicing skills in a context relevant to students' own interests and goals can also help motivate them (Beymer & Thomson, 2015). In the seminar, students picked from a selection of assignments related to the content of the class each week.…”
Section: Forming a Data-science Identitymentioning
confidence: 99%
“…When students have opportunities to exercise their autonomy and make choices while learning, their intrinsic motivation increases (Guthrie et al, 2004). They take ownership and try harder than students who are not provided choices (Beymer & Thomson, 2015). Providing choice leads to outcomes such as increased effort, improved task performance, perceived competence, and preference for challenge (Patall et al, 2008).…”
Section: Increasing Reading Motivation In the Classroommentioning
confidence: 99%
“…Autonomy-supportive actions include behaviors such as providing choice and minimizing the use of controls (Ryan & Deci, 2000). Providing choice may be the most obvious way to support a person's experience of autonomy (Patall et al, 2008) and choice in the classroom has usually been found to promote autonomy among students (Thompson & Beymer, 2015). Though it is difficult to determine how many higher education faculty utilize student choice or how often, the few studies investigating the scope of the practice found opportunities for student choice were infrequent (Bozack et al, 2008).…”
Section: Student Choice For Autonomymentioning
confidence: 99%